Leadership Development Through Sport : Kajian dalam Analisis Bibliometrik - Halizsa, Rahma Nurul; Ma’mun, Amung; Nugraha, Reshandi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
The purpose of this study is to determine the analysis of the study of the development of sports leadership from time to time based on previous research literature in several indexed research journals. This study uses bibliometric analysis through software, namely Vosviewers for effective research results. The research procedure is presented with network visualization, overlay visualization, and density visualization. The stage of collecting articles through the Publish or Perish database consisting of Google Scholar and Taylor and Francis. The types of articles obtained are in the form of indexed article references in Scopus (Q1-Q4) and Sinta (S1-S4). The results of the search analysis found 288 articles over the last 10 years from 2014 to 2024 on leadership and development through sport, then the results showed a positive trend that was systematically arranged into future development topics that were relevant to the research study. Based on data analysis, it can be concluded that leadership development in sports has spread from year to year which is applied in education, sports management and sports political policies, the determination of leadership can also improve one of the life skills factors and can guarantee the quality of life in the future. Keywords : Development through sport, Leadership, Sports, Vosviewer